2012
DOI: 10.3844/ajessp.2012.376.384
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular Storm Sewer Design Under Equal Sediment Mobility

Abstract: Rectangular storm sewers are conduits delivering water to outfall locations and have sizes that are typically larger than standard pipes, by which they become subject to more sediment deposits during operation and thus require higher flow strengths to maintain the bed clean. This study suggests a design procedure of self-cleansing rectangular sewers based on maintaining a lower limit of Shields stress and an upper limit of dimensionless bedload transport capacity. The lower limit of Shields stress is proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Many researchers have undertaken various experimental and empirical studies on sediment transport without sediment [6][7][8][9][10][11][12][13][14]. It can be said that classic methods do not have the capacity to estimate the flow velocity that prevents sediment deposition under different conditions, and there is a need for methods with such capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have undertaken various experimental and empirical studies on sediment transport without sediment [6][7][8][9][10][11][12][13][14]. It can be said that classic methods do not have the capacity to estimate the flow velocity that prevents sediment deposition under different conditions, and there is a need for methods with such capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Azamathulla et al (2012) used a multiple regression model and an adaptive neuro-fuzzy inference system (ANFIS) to predict the functional relationships of sediment transport in sewer pipe systems, which showed that the ANFIS approach gives more satisfactory results compared to previous methods. Almedeij (2012) suggested a self-cleansing design procedure for rectangular sewers based on the sediment transport theory. Ota and Perrusquía (2013) studied sediment transport at the limit of deposition in sewers, which suggested a modified dimensionless bed shear stress equation.…”
Section: Introductionmentioning
confidence: 99%